Anionic Hosts for the Incorporation of Cationic Guests. Issue 10 (25th January 2018) - Peresypkina, Eugenia; Heindl, Claudia; Virovets, Alexander; Brake, Helena; Mädl, Eric; Scheer, Manfred
Abstract: Pentaphosphaferrocene [Cp*Fe(η 5 ‐P5 )] (1 a ) represents an excellent building block for the template‐directed synthesis of spherical supramolecules. Here, the self‐assembly of1 a with Cu I and Cu II halides in the presence of the template complexes [FeCp2 ][PF6 ], [CoCp2 ][PF6 ] and [CoCp2 ] is reported, testifying to the redox behavior of the formed supramolecules. The oxidation or reduction capacity of these reactive complexes does not inhibit their template impact and, for the first time, the cationic metallocene [CoCp2 ] + is enclosed in unprecedented anionic organometallic hosts. Furthermore, the large variety of structural motifs, as icosahedral, trigonal antiprismatic, cuboidal and tetragonal antiprismatic arrangements of1 a units are realized in the supramolecules [FeCp2 ]@[{1 a }12 (CuBr)17.3 ] (3 ), [CoCp2 ] + 3 {[CoCp2 ] + @[{1 a }8 Cu24.25 Br28.25 (CH3 CN)6 ] 4− } (4 ), {[Cp2 Co] + @[{1 a }8 (CuI)28 (CH3 CN)9.8 ]}{[Cp2 Co] + @[{1 a )}8 Cu24.4 I26.4 (CH3 CN)8 ] 2− } (5 ), and [{1 a }3 {(1 a )2 NH}3 Cu16 I10 (CH3 CN)7 ] (6 ), respectively. Abstract : Enclosed for business : For the first time, cationic metallocenes are enclosed in organometallic host molecules as demonstrated by the example of a cobaltocenium cation. In response to the positive charge of the guest molecules, unprecedented anionic hosts are formed.